Decision making in the sri lankan schools of the programme of school improvement is being: a case study with reference to the matara district schools - Arachchi, C.K.; Edirisinghe, S.D. (University of Jaffna, 2012)
: In 2006, the Ministry of Education of Sri Lanka implemented the Programme of School Improvement (PSI) in the government schools in Sri Lanka. In order to gain success of the PSI, School Development Committee (SDC) and School Management Team (SMT) were introduced as the main decision making bodies in those schools. Participatory decision making is one of the key elements of the PSI system. Current decision making process is rather different than the earlier decision making in the government schools in Sri Lanka. Therefore the studying about the decision making process in the PSI schools is imperative. This study design to investigate the nature of the decision making process in the schools where the Programme of School Improvement (PSI) is being implemented. This study used a qualitative case study approach to study the research problem with special reference to the Matara district PSI implemented schools. Purposive sampling technique was employed to select participants in this study, and data were analysed using thematic analysing technique. The measurement of community involvement in SDCs provides some indicators of low community involvement in decision making and management. The mechanism of selection of the members for the SDCs is not transparent, and the community of schools lacks knowledge of the selection process in the SDCs and PSI concept. According to the responses of the majority of the past pupils, the parents and the teachers of SDCs and principals influence to select members for the SDCs in the PSI schools. Thus, it seems that there is no democratic and genuine participatory decision making process in the PSI schools. Moreover, the situation in the SDC meetings is also not much participative. It is needed for drawing attention of higher authority on PSI implementation since now this implementation is taking place without any proper supervision.
Keywords: Decision making; Programme of school Improvement; School based management; Participatory decision making